1994
DOI: 10.1017/s0252921100078076
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration from Field-Aligned Potential Drops

Abstract: Unstable field-aligned currents are seen as the origin of field-aligned potential drops. They convert energy stored in magnetic shear stresses into kinetic energy. A good fraction of this energy is carried by runaway electrons and ions out of the acceleration region. The paper emphasizes the analogy with mechanical fractures. Simple expressions for the energy conversion rate and the parallel potential drop are derived, the two being linked by the critical current density needed for instability. The origin of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 27 publications
0
40
1
Order By: Relevance
“…Through resonant cyclotron interactions of the particles with the waves, electrons and protons will be pitch angle scattered into the loss cone (see Tsurutani and Lakhina, 1997) and lost into the upper atmosphere . Other mechanisms are the generation and damping of AlfvĂ© n waves (Haerendel, 1994) and field-aligned current intensifications and dissipation (Araki, 1994). We refer the interested reader to recent experimental observations of a shock aurora by Motoba et al (2009).…”
Section: Ffss and Dayside Aurorasmentioning
confidence: 99%
“…Through resonant cyclotron interactions of the particles with the waves, electrons and protons will be pitch angle scattered into the loss cone (see Tsurutani and Lakhina, 1997) and lost into the upper atmosphere . Other mechanisms are the generation and damping of AlfvĂ© n waves (Haerendel, 1994) and field-aligned current intensifications and dissipation (Araki, 1994). We refer the interested reader to recent experimental observations of a shock aurora by Motoba et al (2009).…”
Section: Ffss and Dayside Aurorasmentioning
confidence: 99%
“…The key parameters characterizing auroral arcs are based on two crucial assumptions. The first one is that the free energy content of a flux tube above an auroral arc is drained by the energy conversion process in the acceleration region, or “fracture zone”, within 4 AlfvĂ©n transit times, τ A , from equator to ionosphere [see also Haerendel , 1994]. The other one is that during that period practically all free energy (i.e., the fraction ÎŽ ), magnetic and internal, is converted into kinetic energy of the particle beams.…”
Section: Basic Relationsmentioning
confidence: 99%
“…The basic concept is that the band of enhanced conductivity acts as a transformer converting energy stored in the equatorward moving plasma and field into energy of an arc‐associated Boström Type II current system, inside which it is largely consumed by the auroral acceleration process and to a lesser extent fed into longitudinal shear stresses and associated internal energy of the source plasma. If this gain were sufficiently large, one should expect to see an effect on the arc's proper motion, which the author has interpreted as the manifestation of the release of shear stresses and magnetic energy from the region adjacent to the arc [see Haerendel , 1994; Haerendel et al , 1993; Frey et al , 1996]. However, this proper motion would be much slower than assumed in the model of Rothwell et al [1988].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore magnetic shearing may occur between those distorted magnetic field lines and the field lines at lower L shells. Haerendel [1994] has shown that this magnetic shearing can generate field‐aligned currents due to the decoupling of the plasma, which allows fast stress relief. The generation of the unstable field‐aligned currents is a process that converts energy stored in magnetic shear stresses initiated from the shock compression into kinetic energy.…”
Section: Possible Mechanisms Of Particle Precipitation and Auroral Formsmentioning
confidence: 99%